Implementasi Kebijakan Kabupaten Layak Anak di Kabupaten Sinjai Provinsi Sulawesi Selatan - Sakrawandi; Suryono, Agus; Muslim, Abd. Qadir (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2024)
In Order to Fulfilment of children's rights needs to be considered in welcoming demographic bonuses. The KLA policy in Sinjai District has been implemented since 2017-2023. Presidential Regulation No. 25 of 2021 concerning KLA is a system development system that ensures the fulfilment of children's rights and the protection of children that is done in a planned, comprehensive, and sustainable manner. Research method: qualitative method with a descriptive approach. Collecting data collection with observation, interviews, and documentation. Data analysis technique using the Miles, Hubberman, and Saldana model involves collecting data, condensing data, presenting data, and drawing conclusions. data collection, data condensation, data presentation, and conclusion drawing. The purpose of this research is to see the extent to which the successful implementation of the policy implementation in Sinjai Regency. The findings of this study in the implementation of KLA policies in Sinjai District did not run effectively based on analysis with Grindle's theory, the researcher concluded that in terms of policy content, everything has been clearly stated in the policy but the implementers have not been able to implement it effectively while in terms of context, the lack of regulations that have not supported the implementation of the KLA program, the lack of understanding of the actors involved regarding their duties and responsibilities is a problem in policy implementation, the lack of monitoring of the institutions involved, such as the Children's Forum at the village / kelurahan level, is a serious problem. The general lack of public understanding of KLA also adds to the problems in policy implementation.